(untitled) (Scientific journal of the Fergana State University, 2024)
This article presents the length-weight relationships of spotted thicklip loach (Triplophysa strauchii) collected from the ditches of the Fergana Region. Measurements were calculated in terms of total length (to the nearest 0.01 cm) and total weight (to the nearest 0.01 g). Parameters of the length-weight relationship were determined using a linear logarithmic regression model of length versus weight, where values of b greater than and less than 3 for the regression slope indicate positive and negative allometric growth, respectively. In the results of the research, it was found that the indicators of b range from 2,832 (Rishton District) to 3,174 (Uzbekistan District). Correlation coefficient (r2) values ranged from 0,957 to 0,997, indicating a strong positive relationship between length and weight.